The Impacts of Advancements in Digital Technologies on Students’ Self-Regulated Learning - Zhao, Peter Ben Djun (Curtin University, 2021)
This study examined student digital technology usage and student self-regulated learning in 2012 and 2020. Digital technologies have become a staple in both our learning environment, as well as our personal environment. In order to promote and enhance student self-regulated learning, two domains were examined in this study: the student’s personal environment and the educational provider’s learning environment. This holistic examination led to the development a Dual Model of Self-Regulated Learning for supporting student learning.